The White Paper on a National Health Service (letter) - Trades Union Congress; Hartley, J. W.
1944-06-19 1944 1940s 2 pages Chorley Division Trades Council (28 AFFILIATED SOCIETIES) President : MR. J.A. LUCAS. Financial Secretary : Mr. W. CORCORAN. Vice-President : MR. T. GRIME. Counc. J.W. HARTLEY, J.P. 67 YARROW ROAD, Hon. Corres. Secretary. CHORLEY, TRADES UNION CONGRESS and Lancs. & Cheshire Federation of Trades Councils. 19th June 1944 Dear Sirs, THE WHITE PAPER ON A NATIONAL HEALTH SERVICE At the monthly meeting of the above council held on Wednesday the 7th inst; the delegate to the Lancs. & Cheshire Federation in giving his report of the Quarterly Meeting held at Manchester on the 3rd June, dealt at some length with the discussion that took place at that meeting relative to the attitude of the British Hospitals Association and the British Hospitals Contributory Schemes Association to the White Paper recently published. It was reported that the B.H.A. had declared that the White paper was, in its present form, unacceptable to them in many respects and had consequently decided to launch a nation wide publicity campaign estimated to cost about £10,000 in order to give effect to their opposition. Further to this it was also reported that the British Hospitals Contributory Schemes Association had decided to launch a similar campaign following a Special Meeting they held in Birmingham on the 18th of April this year. At this meeting it was reported that many of the speakers [intmated] intimated that they were expressing the views of their contributors on this matter, when in actual fact it is questionable whether a single contributory scheme has called a meeting of its contributors to ascertain the views of its members on the Government's Proposals. It was further reported that at the very same meeting a motion by the Manchester District Area Group of the Contributory Schemes Association, carried by an overwhelming majority the following resolution: "That this meeting of the British Hospitals Contributory Schemes Association, having in mind the potent and incomparable history of Voluntary Hospitals and Contributory Schemes; so strongly praised by the Parliamentary Secretary to the Ministry of Health, coupled with supporting speeches by Members of Parliament in the House of Commons, and of nobility in the House of Lords, feel it incumbent upon them to attempt the formation of an 'ad hoc' Committee, comprising the British Medical Association, the British Hospitals Association and the British Hospitals Contributory Schemes Association. Such Committee to be charged with the immediate preparation of :- (cont.) 292/847/2/50